Joint effects of recent stressful life events and adverse childhood experiences on perinatal comorbid anxiety and depression - Yanyan Hou; Mengqing Shang; Xiayan Yu; Yue Gu; Haiyan Li; Mengjuan Lu; Minmin Jiang; Hualong Zhen; Beibei Zhu; Fangbiao Tao (BMC, 2023)
Abstract Background Stressful life events (SLEs) and adverse childhood experiences (ACEs) have been reported to be associated with perinatal depression (PND) or perinatal anxiety (PNA) alone; however, in most cases, majority of PND and PNA coexist and could lead to more serious health consequences. The independent effect of recent SLEs and their joint effects with ACEs on perinatal comorbid anxiety and depression (CAD) remain inadequately explored. Methods Based on a longitudinal study, 1082 participants receiving prenatal care in Ma'anshan, China were included. Women were recruited in the first trimester (T1: ≤14+ 6 weeks) and followed up at 15 ~ 27 weeks (T2), 28 ~ 40 weeks (T3), and postpartum (T4). Depression and anxiety status were assessed at all time points, while recent SLEs and ACEs were measured at T1. Logistic regression was conducted to examine the associations of SLEs with the risks of CAD at different time points, as well as their joint effects with ACEs on CAD. Results Approximately 38.5% of women experienced at least one SLE, which was significantly associated with higher risks of CAD at all time points (p < 0.05). As the number of SLEs increased, the risk of CAD increased (p for trend < 0.05). Specific types of SLEs were associated with CAD in different periods, while only interpersonal events were consistently associated with risks of CAD throughout the whole perinatal period. The joint effects of SLEs with ACEs on CAD were identified throughout the perinatal period, with the highest observed in the first trimester (aOR = 7.47, 95% CI: 3.73-14.95; p for trend < 0.001). Conclusion Our study demonstrated independent associations of recent SLEs and their joint effects with ACEs with risks of perinatal CAD. SLEs combined with ACEs should be recognized as a major risk factor for perinatal CAD and managed at the earliest time to prevent and control CAD.